2020
DOI: 10.3389/fbioe.2020.565311
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Conversion of Saline Phenol-Containing Wastewater Under Thermophilic Conditions in a Membrane Bioreactor

Abstract: Closing water loops in chemical industries result in hot and highly saline residual streams, often characterized by high strength and the presence of refractory or toxic compounds. These streams are attractive for anaerobic technologies, provided the chemical compounds are biodegradable. However, under such harsh conditions, effective biomass immobilization is difficult, limiting the use of the commonly applied sludge bed reactors. In this study, we assessed the long-term phenol conversion capacity of a lab-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Secondary metabolites in the liquid medium (acetate, propionate, butyrate, and valerate) were measured by gas chromatography (7890A GC; Agilent Technologies, United States) according to the method described by Muñoz Sierra et al (2020) . The gas composition of samples stabilized at atmospheric conditions was determined via gas chromatography (7890A GC; Agilent Technologies, United States) using a thermal conductivity detector operated at 200°C and oven temperature ramping from 40 to 100°C.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary metabolites in the liquid medium (acetate, propionate, butyrate, and valerate) were measured by gas chromatography (7890A GC; Agilent Technologies, United States) according to the method described by Muñoz Sierra et al (2020) . The gas composition of samples stabilized at atmospheric conditions was determined via gas chromatography (7890A GC; Agilent Technologies, United States) using a thermal conductivity detector operated at 200°C and oven temperature ramping from 40 to 100°C.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary metabolites, i.e., acetate, propionate, butyrate and valerate were measured from filtered (0.45 μm) liquid samples by gas chromatography (7890A GC, Agilent Technologies, US) according to [ 97 ]. The detection limits for these compounds were 12, 16, 18 and 23 mg L −1 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The membrane module was operated with a cross-flow velocity of 0.8 ± 0.1 m⋅s − 1 and a constant flux of 4.0 LMH (Q = 1 L/d). The inoculum biomass was obtained from a full-scale UASB reactor treating petrochemical wastewater (Shell Moerdijk, The Netherlands), and it was acclimated and used in previous experiments [29]. The reactor was mixed thoroughly by biomass recirculation at a rate of 200 d − 1 .…”
Section: Anaerobic Membrane Bioreactormentioning
confidence: 99%
“…Previous research showed the feasibility of phenol degradation under saline and thermophilic conditions [29]. Nevertheless, there is a lack of understanding of the process, which is needed for guaranteeing process stability.…”
Section: Introductionmentioning
confidence: 99%